2000
DOI: 10.1021/la000141e
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Adsorption of Monodendron-Jacketed Linear Polymers on Highly Oriented Pyrolytic Graphite

Abstract: Linear polymers with monodendron side groups adsorb on highly oriented pyrolytic graphite (HOPG) in a remarkably regular pattern. The wormlike molecules have been depicted individually by scanning force microscopy with their long axis aligned according to the 3-fold symmetry of HOPG. The positional and orientational order of the adsorbed molecules is explained by the specific interaction of the alkyl substituents of the monodendrons with the HOPG surface. Direct evidence of the epitaxial adsorption was found b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
75
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 30 publications
0
75
0
Order By: Relevance
“…Due to the presence of hydrophilic and hydrophobic residues, the adsorption of proteins and associating polymers on a surface is more complicated than the adsorption of homopolymers. 14 For example, Bauerle et al 15 and Prokhorova et al 16 observed monolayers with long-range order when oligo͑thiophenes͒ or comblike polymers adsorb on graphite, while Sheiko et al 17 reported first-order rod-globule phase transitions in adsorbed polymer films. When adsorbed on a surface, proteins often undergo conformational changes in an attempt to lower the global free energy.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the presence of hydrophilic and hydrophobic residues, the adsorption of proteins and associating polymers on a surface is more complicated than the adsorption of homopolymers. 14 For example, Bauerle et al 15 and Prokhorova et al 16 observed monolayers with long-range order when oligo͑thiophenes͒ or comblike polymers adsorb on graphite, while Sheiko et al 17 reported first-order rod-globule phase transitions in adsorbed polymer films. When adsorbed on a surface, proteins often undergo conformational changes in an attempt to lower the global free energy.…”
Section: Introductionmentioning
confidence: 99%
“…[1] SFM is now routinely used to visualise rather stiff and thick synthetic macromolecules, e.g., of monodendron-jacketed, dendronized, helical, and hyperbranched polymers, etc. [2] Certain progress has been also achieved in the SFM-imaging of flexible synthetic polymer chains: their conformational transitions have been studied ex situ, provided that strong binding (e.g., by electrostatic forces) of the macromolecules to the supporting substrate has been ensured. [3] But the in situ SFM-visualisation of the macromolecular conformational dynamics remains a rather challenging task requiring a search for more appropriate experiments.…”
Section: Introductionmentioning
confidence: 99%
“…[33,34] In addition, the dendron provides a significant mechanical barrier to rotation about bonds in a central unit when the conjugates are in a conformationally restricted environment, such as in a solid-state lattice or on a surface. We have shown that when monolayers of these systems form, not only a pattern containing one molecular conformation (in a global energy minimum), but a range of conformations may be found in surface-bound domains.…”
mentioning
confidence: 99%